Design, Analysis, and Implementation of the Subdivision Interpolation Technique for the Grating Interferometric Micro-Displacement Sensor - Jiuhui Tang; Haifeng Peng; Peng Yang; Shangzhou Guo; Wenqiang Sun; Li Jin; Kunyang Xie; Mengwei Li (Photonics)
A high-resolution grating interferometric micro-displacement sensor utilizing the subdivision interpolation technique is proposed and experimentally demonstrated. As the interference laser intensity varies sinusoidally with displacement, subdivision interpolation is a promising technique to achieve micro-displacement detection with a high resolution and linearity. However, interpolation errors occur due to the phase imbalance, offset error, and amplitude mismatch between the orthogonal signals. To address these issues, a subdivision interpolation circuit, along with 90-degree phase-shifter and high-precision DC bias-voltage techniques, converts an analog sinusoidal signal into standard incremental digital signals. This novel methodology ensures that its performance is least affected by the nonidealities induced by fabrication and assembly errors. Detailed design, analysis, and experimentation studies have been conducted to validate the proposed methodology. The experimental results demonstrate that the micro-displacement sensor based on grating interferometry achieved a displacement resolution of less than 1.9 nm, an accuracy of 99.8%, and a subdivision interpolation factor of 208. This research provides a significant guide for achieving high-precision grating interferometric displacement measurements.